'Herbals she peruseth': reading medicine in early modern England. Issue 4 (September 2014) - Leong, Elaine
<x xml:space="preserve">Abstract</x> In 1631, Richard Brathwaite penned a conduct manual for 'English Gentlewomen'. In Brathwaite's mind, the ideal English gentlewoman was not only chaste, modest and honourable but also an avid reader. In fact, Brathwaite specifically recommends English gentlewomen to first peruse herbals and then to deepen their medical knowledge via conference. Centred on the manuscript notebooks of two late seventeenth‐century women, Margaret Boscawen (d. 1688) and Elizabeth Freke (1642–1714), this article explores women and 'medical reading' in early modern England. It first demonstrates that whilst both women consulted herbals by contemporary authors such as John Gerard and Nicholas Culpeper, their modes of reading could not be more different. Where Freke ruminated, digested and abstracted from Gerard's large tome, Boscawen made practical lists from Culpeper's The English Physitian. Secondly, the article shows that both supplemented their herbal reading with a range of other vernacular medical texts including printed medical recipe books, contemporary pharmacopoeia and surgical handbooks. Early modern English women's medical reading, I argue, was nuanced, sophisticated and diverse. Furthermore, I contend that well‐informed readers like Boscawen and Freke made smart medical consumers and formidable negotiators in their medical encounters.